Pengaruh Soft Skill Terhadap Kesiapan Kerja Mahasiswa Universitas Bandar Lampung - Khairudin; Putri Ismatul I’fa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this research is to find out how soft skills influence the preparation of Bandar Lampung University students to enter the world of work. This research uses a quantitative descriptive method. 365 students from two study programs namely accounting and management represent the population in this survey, all of them are 2019 FEB students. The sample was obtained using a probability random sampling technique, and a total of 78 respondents were obtained which were then analyzed using SPSS 26 software. The results of the study revealed that soft skills have a positive and significant impact on student work readiness in February 2019. according to the regression coefficient of 0.832, the calculated t value of 10.589, and the correlation coefficient value of 0.772. The coefficient of determination (R2) for students at the University of Bandar Lampung is 0.591 or 59.1%, which proves that soft skills can affect changes in work readiness variables by 59.1%. Meanwhile the remaining 40.9% is described by factors outside this study.